The effectiveness and safety of treatments used for acute diarrhea and acute gastroenteritis in children: protocol for a systematic review and network meta-analysis (2016)
ABSTRACT: Background: Acute diarrhea and acute gastroenteritis (AD/AGE) are common among children in low- and middleincome countries (LMIC) and high-income countries (HIC). Supportive therapy including maintaining feeding, prevention of dehydration, and use of oral rehydration solution (ORS), is the mainstay of treatment in all children. Several additional treatments aiming to reduce the episode duration have been compared to placebo, but the differences in effectiveness among them are unknown. Methods and analysis: We will conduct a systematic review of all randomized controlled trials evaluating the use of zinc, vitamin A, probiotics, prebiotics, synbiotics, racecadotril, smectite, and fermented and lactose-free milk/ formula for AD/AGE treatment in children. The primary outcomes are diarrhea duration and mortality. Secondary outcomes are diarrhea lasting 3 or 7 days, stool frequency, treatment failure, hospitalizations, and adverse events. We will search MEDLINE, Ovid EMBASE, CINAHL, the Cochrane Central Register of Controlled Trials (CENTRAL), and LILACS through Ovid, as well as grey literature resources. Two reviewers will independently screen titles and abstracts, review full texts, extract information, and assess the risk of bias (ROB) and the confidence in the estimate (with the grading of recommendations, assessment, development, and evaluation [GRADE] approach). Results will be summarized narratively and statistically. Subgroup analysis according to HIC vs. LMIC, age, nutrition status, and ROB is planned. We will perform a Bayesian network meta-analysis to combine the pooled direct and indirect treatment effect estimates for each outcome, if adequate data is available. Discussion: This is the first systematic review and network meta-analysis that aims to determine the relative effectiveness of pharmacological and nutritional treatments for reducing the duration of AD/AGE in children. The results will help to reduce the uncertainty of the effectiveness